Gestión administrativa y su impacto en el compromiso laboral de la Importadora Ilga matriz Guayaquil - Onofre Martillo, Joselin Cecilia (2020)
This research project was developed to identify the impact that administrative management has on labor commitment within Importadora Lino Gamboa, where it was possible to identify a problem that emphasizes inadequate leadership management by department heads. , the staff lacks motivation and training to be able to carry out each of the activities that are required to be carried out efficiently and effectively. The main objective is to implement a pilot plan which aims to improve each of the issues raised and thus be able to provide quality service at the Importadora Lino Gamboa (ILGA) in the city of Guayaquil, province of Guayas. The research methodology that was implemented was the survey and the interview where I helped to obtain more solid results that allowed us to analyze the deficiency within the administrative management.